2017
DOI: 10.1016/j.socscimed.2017.04.042
|View full text |Cite
|
Sign up to set email alerts
|

Towards a feminist understanding of intersecting violence against women and children in the family

Abstract: While intimate partner violence (IPV) against women and violence against children (VAC) have emerged as distinct fields of research and programming, a growing number of studies demonstrate the extent to which these forms of violence overlap in the same households. However, existing knowledge of how and why such co-occurrence takes place is limited, particularly in the Global South. The current study aims to advance empirical and conceptual understanding of intersecting IPV and VAC within families in order to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
83
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 35 publications
6
83
0
7
Order By: Relevance
“…This study claimed that empirical evidence suggests that sexist individuals are more accepting violence in social relationships than nonsexist individuals. While we found too that both sexism and acceptability of general violence in social relationships were positively related to acceptability of IPV, our results included dimensions and variables hitherto not yet debated in the public health debate on the subject, namely, the disrespect of property rights and family values (see literature ; Martín‐Fernandez et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This study claimed that empirical evidence suggests that sexist individuals are more accepting violence in social relationships than nonsexist individuals. While we found too that both sexism and acceptability of general violence in social relationships were positively related to acceptability of IPV, our results included dimensions and variables hitherto not yet debated in the public health debate on the subject, namely, the disrespect of property rights and family values (see literature ; Martín‐Fernandez et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Domestic violence against women and violence against children have emerged as distinct fields of research with a growing number of studies demonstrating the extent to which the two overlap in the same household (Namy et., al 2017). They strongly confirm that both acts co-occur in the same households and that women's use violence against children is considered as an acceptable way to control behaviour in line with parents' role to enforce discipline as a normative and important function.…”
Section: Feminismmentioning
confidence: 99%
“…Women's lack of resources also makes them susceptible because what they do, wish to do, plan to do and their reasoning capacity is restricted. Violence towards women in the family also happens to those women who may also have social standing and high income within family contexts (Namy, Carlson, O'Hara, Nakuti, Bukuluki, Lwanyaaga & Michau, 2017). Lobaka (2017) also indicated that men with limited or no limited wealth and resources may resort to physical force or violence more quickly.…”
Section: Literature Reviewmentioning
confidence: 99%